Child behavioural problems and body size among 2-6 year old children predisposed to overweight. results from the "healthy start" study. - Nanna J Olsen (Public Library of Science (PLoS), 2013)
Objective Psychological adversities among young children may be associated with childhood overweight and obesity. We examined if an increased level of child behavioural problems was associated with body size among a selected group of 2-6 year old children, who were all predisposed to develop overweight. Methods Cross-sectional analyses were conducted using baseline data from the "Healthy Start" intervention study. A total of 3058 children were invited to participate, and data from 583 children who were all predisposed for obesity was analyzed. The Danish version of the Strengths and Difficulties Questionnaire (SDQ) was used to assess child stress by the SDQ Total Difficulties (SDQ-TD) score and the Prosocial Behavior (PSB) score. Height and weight were measured, and BMI z-scores were calculated. Results A direct, but non-significant linear trend was found between SDQ-TD score and BMI z-score (β = 0.021, p = 0.11). Having an SDQ-TD score above the 90(th) percentile was associated with BMI z-score (β = 0.36, p = 0.05). PSB score was not associated with BMI z-score. Analyses were adjusted for parental socioeconomic status, parental BMI, family structure, dietary factors, physical activity, and family stress level. Conclusion The results suggested a threshold effect between SDQ-TD score and BMI z-score, where BMI z-score was associated with childhood behavioural problems only for those with the highest scores of SDQ-TD. No significant association between PSB score and BMI z-score was found.